“We need all hands on deck”: characterizing addiction medicine training in Canada—a mixed methods study of fellowship program directors - Clara Lu; Kathryn Chan; Leslie Martin; Nadia Fairbairn (Addiction Science & Clinical Practice)
Abstract Background Addiction Medicine training in Canada has evolved substantially in the last few years with the establishment of accreditation standards and several new fellowship programs. The novelty of these formal training programs, created in response to complex and ever-expanding clinical needs in Addiction Medicine, creates unique educational circumstances that must be understood to support future growth. This study characterizes the current state of these postgraduate training programs in Canada through the perspectives of Program Directors (PDs). Methods This study is a mixed methods study of 12 PDs. In Phase 1, participants completed a quantitative survey analyzed through descriptive statistics. In Phase 2, participants underwent a qualitative semi-structured interview that was coded with a thematic analysis approach. Mixing occurred both during the interim analysis between phases and during the interpretation stage. Results 28 trainees enrolled in a fellowship program in 2021–22 across 10 programs, and 27 trainees enrolled in 2022–23 across 11 programs. In each year, there were significantly fewer available spots than applications (31% and 29%, respectively). PDs identified a funding “bottleneck” as the most difficult and important challenge facing programs, with trainees supported by diverse and unstable funding sources. Qualitative analysis highlighted the need for sustainable funding models, flexibility toward alternative training pathways (shorter durations of training and re-entry from practice), and establishment of a national community of practice to support the co-creation of a robust addictions medical education infrastructure. Conclusion For Addiction Medicine training to meet workforce demands, PDs stressed that funding was the challenge of prime importance. Future studies should examine the perspectives of Addiction Medicine fellows, the clinical and research impacts of fellowship graduates, and the cost-effectiveness of fellowship funding models.